The effects of real exchange rate on trade balance and domestic output: a case of Malaysia - Yusoff, Mohammed (Taylor & Francis, 2010)
The main objective of this study is to determine the effects of real exchange rate changes on the real Malaysian trade balance and the domestic output during the pegged exchange rate regime, 1977:1{1998:2, using quarterly data. The cointegration results suggest that a real ringgit exchange rate depreciation improves the Malaysian balance of trade in the long run.The impulse response analysis suggests that the effects of a depreciation of ringgit on the trade balance and domestic output are quite similar. A devaluation will initially improve the trade balance and domestic output, after which the trade balance starts to deteriorate and then the recession sets in, but subsequently both the trade balance and domestic output improve.